THE INFLUENCE OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN PT. SON KARELLA MARE - Muhammad Pananrangi; Osman Lewangka; Indrianty Sudirman (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
Every company wants high-performing human resources. This study aims to determine the effect of motivation and job satisfaction on employee performance at PT. Putra Karella Mare directly and mediation. This study uses a quantitative approach that aims to explain the position of the variables studied as well as the relationship between one variable with another with the intention to test hypotheses that have been formulated previously. This study will explain the causal relationship between variables through hypothesis testing. In this study, the analysis method used is path analysis (PATH) using the help of the SmartPLS 3.2.8 program. The results found that motivation has a positive and significant effect on job satisfaction, motivation has a positive effect not significant on performance, job satisfaction has a positive and significant effect on performance, motivation has a positive and significant effect on performance if mediated by job satisfaction